Pengaruh Media Flash Card Terhadap Hasil Belajar Siswa Kelas V Mata Pelajaran IPS di SDN Banjarsari 2 - Rika Nurhasanah; Ribut Prastiwi Sriwijayanti; Ryzca Siti Qomariyah (Jurnal Pendidikan Sosial Dan Konseling, 2023)
Learning media is anything that can be used to convey messages from the teacher to students so that they can stimulate the mind, feelings, interests, and students' attention so that the learning process can take place effectively. The problems that occurred at SDN Banjarsari 2 in class V showed that many students tended to feel bored, students looked lacking active in the learning process, and the material presented is difficult for students to understand. It was from here that the researcher was interested in conducting research entitled The effect of flashcard media on the learning outcomes of fifth grade students in social studies at SDN Banjarsari 2. Based on the background of the problems that have been occurs, then it is formulated "Is there any effect of flash card media on the learning outcomes of class V students in the social studies subject at SDN Banjarsari 2. This type of research is quantitative by using an experimental model One Group Pretest Posttest. Data collection techniques in this study are: observation, questionnaire, test, and documentation. Analysis of the data obtained from the results. This study uses descriptive and differential data analysis. Judging from the average score of students before using the flash card media, namely 57.61%, it is in the low category. Meanwhile, after using the flash card media, the average value of students, namely 77.61%, is in the medium category. From the results of inferential statistical analysis using the t-test formula, it can be seen that the tcount is 7.35. With a frequency (dk) of 21-1 = 20, at a significant level of 0.05 obtained ttable = 2.086, therefore tCount > tTable at a significant level of 0.05, then the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted, which means that the application of flash card media affects social studies learning outcomes for fifth grade students at SDN Banjarsari 2.